The Effect of Ease of Transaction, Digital Literacy, and Financial Literacy on The Use of E-Banking - Munari, Shinta Aprilia Lucki Hidayati; Susanti, Susanti (Economic Education Analysis Journal, 2021)
This study aimed to analyze the effect of ease of transaction, digital literacy, and financial literacy on the use of e-banking. This type of research was quantitative research. The population in this study were 298 students. By using purposive sampling technique a sample of 40 Accounting Education students at State University of Surabaya was obtained. Data collection techniques used questionnaires and multiple choice tests. The data analysis technique used was multiple linear regression analysis with the help of SPSS software version 24. The result showed that both simultaneouly and partially ease of transaction, digital literacy, and financial literacy had a significant effect on the use of e-banking.